Lirik Lagu Satru 2 Karya Denny Caknan dari Kacamata Sosiolinguistik - Firdaus Eka Febryanti (Diskursus: Jurnal Pendidikan Bahasa Indonesia, 2022)
In this modern era, there are many songs with lyrics that use Javanese. Modern pop songs with Javanese lyrics are increasingly loved by the public. This is because the songs of the pop genre and in Javanese are considered to represent the feelings of the ambyar, the majority of whom are teenagers (aged around 12-22 years). This study was conducted with the aim of analyzing a Javanese pop song entitled Satru 2 written by Denny Caknan based on a sociolinguistic scalpel. So to achieve this goal, this research uses descriptive qualitative methods. The point of view of sociolinguistic theory is used as a reference in this study. Based on the analysis that has been done, the lyrics of the song Satru 2 are really relevant to the age of the listener who is a teenager. This was found based on the use of dialect aspects, speech levels, and the variety of languages used in the lyrics of the song, thus creating a sense of closeness to the listener. Based on these aspects, the lyrics of the song Satru 2 use the Blitar dialect with the speech level of ngoko.Keywords: Sociolinguistics, Javanese Song, Satru 2, Denny Caknan